Breather Structures and Peregrine Solitons in a Polarized Space Dusty Plasma - Singh, Kuldeep; Saini, N. S. (Frontiers in Physics, 2020)
In this theoretical investigation, we have examined the combined effects of nonthermally modified polarization force on modulational instability of dust acoustic (DA) waves and evolution of different kinds of rogue waves in space dusty plasma containing negatively charged dust as fluid, Boltzmannian electrons and ions obeying Cairns' nonthermal distribution. The nonthermality of ions has considerably altered the influence of polarization force. By employing the multiple-scale perturbation technique, the nonlinear Schrödinger equation (NLSE) is derived to study the the modulational instability (MI) of the dust acoustic waves (DAWs). It is remarked that the impact of polarization force is to narrow the wavenumber domain. The rational solution of NLSE illustrates the evolution of DA breathers including, Akhmediev breathers (AB), Kuznetsov–Ma (KM) breathers and Peregrine solitons (rogue waves). Further, transformation of higher order rogue wave triplets to the super rogue waves due to the superposition is also discussed. It is noticed that amalgamation of polarization force and nonthermal ions have an explicit influence on the evolution of different kinds of DA rogue waves. It is remarked that our present theoretical findings may shed the light on the generation of different kinds of DA rogue waves in laboratory experiments and space, especially in the planetary rings and comet tails.